Timing and drivers of local to regional scale land-cover changes in the hemiboreal forest zone during the Holocene: A pollen-based study from South Estonia. (1st February 2022) - Poska, Anneli; Väli, Vivika; Vassiljev, Jüri; Alliksaar, Tiiu; Saarse, Leili
Abstract: Current land use and climate change pose a threat to the continued provision of ecosystem services expected from terrestrial land cover. Studies on past land-cover responses to such changes provide valuable information for future decisions. The hemiboreal zone, situated between temperate and boreal biomes, is a natural sensitivity hotspot for land cover change: it contains a continuous distribution limit of several temperate ( Quercus robur, Tilia cordata, Fraxinus excelsior, Ulmus glabra, etc.) and some boreal (e.g. Picea abies ) tree species. High resolution pollen data from three lakes in South Estonia, a hemiboreal zone in Northern Europe, was used to reconstruct the climate-driven dynamics of vegetation composition, anthropogenic deforestation, species-specific responses to climate cycles, and plant related environmental variables during the Holocene at a local and regional scale. The Landscape Reconstruction Algorithm (LRA) was used to reconstruct the vegetation composition, the Ellenberg Indicator Values for environmental reconstructions, and the Wavelet analysis for detecting cyclic patterns. The major land cover and environmental changes are in good accordance with the climate-based formal tripartite subdivision of the Holocene: a quick succession of tundra, boreal, and nemoral biomes during the Early Holocene, a dominance of temperate, broad-leaved forests during the Middle Holocene, and an expansion of mixed boreal forests and anthropogenic deforestation during the Late Holocene. Several episodes of compositional turnover ranging from a century (e.g., the transition from wet to dry tundra) to several millennia (e.g., the replacement of the temperate deciduous forests with boreal mixed forests) were identified. Our results show that local community changes have a shorter duration than the regional ones. The introduction of slash-and-burn agriculture caused abrupt forest composition changes at a local scale, promoting early successional tree species, even prior to the establishment of a permanently open cultural landscape. The only late successional tree species favoured by slash-and-burn cultivation was Picea abies . However, the application of more permanent cultivation strategies reduced its representation considerably. The determined cyclic changes in the proportions of tree taxa show, that most late successional trees exhibit high frequency (ca 200–400 year) cyclicity, probably reflecting the stand scale regeneration processes. The observed 1600 ± 200 and 1200 ± 200 year cycle changes in the occurrences of Quercus robur, Ulmus glabra and U. laevis, and Picea abies have a possible connection with a 1500 ± 500 year Bond cycle. Most of the tested tree taxa also had a statistically significant correlation with the ca 2200–2500 year Bray solar forcing cycle. Highlights: A succession of 4 biomes and the Late Holocene distinct deforestation was recorded. Compositional turnover rates of vegetation range from a century to several millennia. Local community changes have higher variation and shorter duration than regional. Tree taxa occurrence is affected by 1500 (Bond) and 2200 (Bray) year climate cycles. Pollen-based Ellenberg Indicator Values reflect well natural environmental conditions.